Experiences of hospital care and treatment seeking for pain from sickle cell disease: qualitative study. Issue 7198 (12th June 1999) - Maxwell, Krista; Streetly, Allison; Bevan, David
Abstract: Objective: To investigate how sociocultural factors influence management of pain from sickle cell disease by comparing the experiences of those who usually manage their pain at home with those who are more frequently admitted to hospital for management of their pain. Design: Qualitative analysis of semistructured individual interviews and focus group discussions. Participants: 57 participants with genotype SS or S/β-thal (44 subjects) or SC (9) (4 were unknown). 40 participants took part in focus groups, six took part in both focus groups and interviews, and nine were interviewed only. Participants were allocated to focus groups according to number of hospital admissions for painful crisis management during the previous year, ethnic origin, and sex. Results: The relation between patients with sickle cell disease and hospital services is one of several major non-clinical dimensions shaping experiences of pain management and behaviour for seeking health care. Experiences of hospital care show a range of interrelated themes, which are common to most participants across variables of sex, ethnicity, and hospital attended: mistrust of patients with sickle cell disease; stigmatisation; excessive control (including both over- and undertreatment of pain); and neglect. Individuals respond to the challenge of negotiating care with various strategies. Patients with sickle cell disease who are frequently admitted to hospital may try to develop long term relationships with their carers, may become passive or aggressive in their interactions with health professionals, or may regularly attend different hospitals. Those individuals who usually manage their pain at home express a strong sense of self responsibility for their management of pain and advocate self education, assertiveness, and resistance as strategies towards hospital services. Conclusions: The current organisation and delivery of management of pain for sickle cell crisis discourage self reliance and encourage hospital dependence. Models of care should recognise the chronic nature of sickle cell disorders and prioritise patients' involvement in their care.